Effects of Maltodextrin on Characteristics of Calamansi Orange Peel (Citrofortunella microcarpa) as A Green Tea Flavor - Devi Silsia; Bosman Sidebang; Ayu Sagita Putri Silalahi (Agroindustrial Technology Journal, 2025)
Calamansi orange peel contains bioactive compounds and essential oils but is often discarded as waste instead of being utilized. This research aims to determine the effect of adding maltodextrin during the drying process on the characteristics of calamansi orange peel and to assess panelists' acceptance of its use as a green tea flavoring. The study employed a Completely Randomized Design (CRD) with one factor, namely maltodextrin concentration (6%, 8%, 10%). Drying was carried out for 7 hours using an oven at 60 ⁰C. The organoleptic test was conducted by brewing 3 g of a mixture of green tea and calamansi peel powder in a 1:2 ratio in 220 ml of hot water at a temperature of 85 ⁰C for 5 minutes. The results showed that the calamansi peel powder had a moisture content of 1.41–3.41%, vitamin C content of 58.67–108.53 mg/100g, and volatile reducing substance (VRS) content of 6.5–12 meq. The highest level of panelists' preference for calamansi powder as a green tea flavoring was observed in the treatment with the addition of 10% maltodextrin, ranging from "liked" to "very liked."